2013
DOI: 10.1063/1.4819482
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric and ferroelectric characteristics in Ca-modified BaTiO3 ceramics

Abstract: Ultrahigh strain and piezoelectric behavior in relaxor based ferroelectric single crystals Journal of Applied Physics 82, 1804 (1997) Synergic modification of BaTiO 3 ceramics was investigated by Ca-substitution, and the superior dielectric and ferroelectric properties were determined together with the structure evolution. X-ray diffraction (XRD) analysis demonstrated a large solubility limit above x = 0.25 in Ba 1−x Ca x TiO 3 solid solution where the fine grain structure was observed with increasing x. Room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 27 publications
5
59
0
Order By: Relevance
“…The compositions x=0.05 and 0.075 show the maximum values of J max as 4.71910 À5 A/cm 2 and 3.61910 À5 A/cm 2 , respectively. 12 Further, as Sn 4+ content increases from x=0.025 to 0.1, the observed E c values are in the range, 5.77 kV/cm-4.34 kV/cm, which indicates that these ceramics are relatively easy to pole and hence it may be possible to achieve better piezoelectric and electrostrictive properties. On the other hand, the compositions with x=0.00 and 0.1 does not show any intersection of P-E and J-E plots.…”
Section: Ferroelectric Propertiesmentioning
confidence: 86%
See 3 more Smart Citations
“…The compositions x=0.05 and 0.075 show the maximum values of J max as 4.71910 À5 A/cm 2 and 3.61910 À5 A/cm 2 , respectively. 12 Further, as Sn 4+ content increases from x=0.025 to 0.1, the observed E c values are in the range, 5.77 kV/cm-4.34 kV/cm, which indicates that these ceramics are relatively easy to pole and hence it may be possible to achieve better piezoelectric and electrostrictive properties. On the other hand, the compositions with x=0.00 and 0.1 does not show any intersection of P-E and J-E plots.…”
Section: Ferroelectric Propertiesmentioning
confidence: 86%
“…dielectric constant (e r ) and dielectric loss (tan d) were measured from À100°C to 150°C, at 100 kHz shown in Figure 2. 12 The peaks correspond to T O-T and T R-O are observed below (e r ) max for x=0.05 and x=0.075 (Figure 2C-D). This revealed that the T C remains almost unchanged for x=0.00 and x=0.025, whereas the orthorhombic-tetragonal (T O-T ) and rhombohedra-orthorhombic (T R-O ) may be shifted below À100°C.…”
Section: Dielectric Propertiesmentioning
confidence: 91%
See 2 more Smart Citations
“…B-site substitution often comes from metal ions (Sn 4+ ) and (Zr 4+ etc.). [6] The effects of Mn-substitution in BaTiO 3 are quite unique, and the increasing interests have been received recently. [7] However, doped MnO 2 can exhibit competitive ferroelectric with the benefit of being lead free.…”
Section: Introductionmentioning
confidence: 99%